THERMODYNAMIC COSMOLOGY - Criss R.E.; Hofmeister A.M. (My University, 2001)
The universe is an isolated system with constant mass-energy. The second law of thermodynamics requires that its entropy must increase over time-that is, the universe is irreversible-yet modern cosmological models presume isentropy. Entropy production due to expansion of the universe is calculable and negligible, but enormous entropy is created as matter is converted to energy and irreversibly transferred from hot stellar interiors to cold dark matter. Although the rate of entropy increase must eventually diminish, entropy production may be nearly linear at this time. Previous omission of entropy production from the cosmological equations is the source of ''reversible'' time and has led to the misconceptions that the universe is expanding and that a big bang is necessary. Instead, the evolution of the universe is guided by irreversible mass loss through stellar burning, which requires contraction, as is observed among our local group of galaxies.A new equation for the mass of the universe gives a result that is in good agreement with previous equations and with extrapolated densities and that leads to the conclusion that the binding energy of matter to the universe is equal to its rest energy. The microwave background radiation does not require a big bang but instead is consistent with blackbody emissions from dark matter (cavity radiation) that is warmed to 2.7 K by radiative transfer from the stars; such a balance of flux is required by the zeroth law. The evolution of the universe, being irreversible, is best described as the self-organization of a nonequilibrium system with ordering through fluctuations and dissipative structures. Complexity behavior is implicit in the dominance of matter over antimatter, the archetypical birfurcation, and in the spiral forms of the galaxies, a pattern expected for asymptotic stability.